Transient Parvovirus B19 DNAemia After Kidney Transplantation: A 2-Sided Story. (14th February 2023) - Russcher, Anne; Molenaar-de Backer, Marijke; de Brouwer, Caroline; Dijkstra, Kyra; Kers, Jesper; de Vries, Aiko; Zaaijer, Hans; Vossen, Ann; Kroes, Aloysius
Abstract: Parvovirus B19 (B19V) DNAemia appears to be a relatively common finding after kidney transplantation. However, not all DNAemia signifies active infection with replicating virus. This study screened 134 patients posttransplantation for B19V DNAemia and identified 2 cases in which viral DNA was present after transplantation, with the donor kidney as probable source of the DNA. In both cases intact viral particles could not be detected using an endonuclease method, indicating the presence of noninfectious DNA remnants.